A Study on the Creep Strength of L12 and B2-ordered Intermetallics - 한성오; 한창석 (대한금속·재료학회지, 48(12), 2010)
The creep rates of polycrystalline L12-ordered Co3Ti and B2-ordered NiAl-Hf intermetallics decrease appreciably with the fine precipitation of the coherent disordered fcc Co-rich phase and Ni2AlHf phase. With B2-ordered NiAl containing L21-Ni2AlHf precipitates, transmission electron microscope observations of the interaction between dislocations and spherical precipitates revealed that the dislocations tend to be strongly attracted to the particle interfaces during the creep deformation. On the other hand, with L12-ordered Co3Ti, the significance of the threshold stress is discussed based upon the transmission electron microscope observations of the interaction between dislocations and precipitates. The superdislocations produced during deformation tend to be strongly attracted and dissociated as they meet the coherent disordered precipitates because the anti-phase boundary energy in the disordered phase was zero. An extra force required to pull the dislocations out of the disordered particles during the creep deformation establishes the threshold stress which is beneficial for improving creep strength under lower stresses. KCI Citation Count: 6